Analisis Efektivitas Pengembangan Bahan Ajar Fisika dengan Konten Kecerdasan Sosial pada Materi Gerak Parabola, Gerak Melingkar dan Hukum Newton untuk Kelas X SMA - Hira Khairunnisa; Zulhendri Kamus; Murtiani M.Pd (Universitas Negeri Padang, 2018)
The 2013 curriculum is designed in order that the students have all competencies, which include spiritual competency, social attitude, knowledge, and skill. Social competency is an important competency to be developed in learning the physics materials. In the process of learning physics, it is required learning materials contain social intelligence values. However, learning materials at schools have not put the values of social intelligence based on the 2013 curriculum. This study aims at producing physics teaching materials with content of social intelligence on parabolic motion, circular motion and Newton's law. The type of research is research and development (R & D). The object of this study is teaching materials with the content of social intelligence in physics learning in grade X high school students. These research and development steps consist of ten steps. However, in this research was limited to the sixth step that is until the trial of the product. The instrument used are validity test sheet and effectiveness test sheet. Based on data analysis, there are two conclusions obtained. First, the teaching materials of physics with contents of social intelligence values developed in accordance with the structure of teaching materials and have a high value. Based on the value given by the validator obtained an average of 85.5 with very high category. Second, teaching materials of physics with the content of social intelligence values developed effective used in the study physics. This can be seen from the increased aspects of knowledge after using the teaching materials of physics with the content of social intelligence values.